Foster Parent Development Model Approach to Strengthen Pancasila Character Values to Form the Estuary Spirit and Identity of Poltekip Cadets of the Ministry of Law and Human Rights - Tri Budi Haryoko; Encep Syarief Nurdin; Yadi Ruyadi; Tri Suhartati (Universitas Negeri Malang, 2025)
This study aims to evaluate the effectiveness of the foster guardian model in strengthening Pancasila character values, esprit de corps, and identity among cadets of the Correctional Sciences Polytechnic (Poltekip) of the Ministry of Law and Human Rights. Using a qualitative descriptive design with a case-study approach, data were collected through in-depth interviews, field observations, and document analysis involving cadets, foster guardians, and instructors. The analysis employed triangulation to ensure the credibility and validity of findings. The results show that the foster guardian model contributes positively to the internalization of Pancasila values by promoting discipline, responsibility, and personalized mentoring. However, its implementation is constrained by the limited number of mentors, the absence of a standardized mentoring curriculum, and inadequate supporting facilities, particularly the lack of dormitories that hinder continuous supervision. The study also found that esprit de corps develops more strongly in structured and communal environments, while family involvement in character formation remains limited. To address these challenges, strategies such as strengthening alumni participation, enhancing the mentoring capacity of lecturers, and adopting a community-based cultural approach are recommended. In conclusion, effective character development for Poltekip cadets requires synergy between institutional systems, competent mentors, and a supportive social environment. The findings highlight the need for a more integrative and sustainable foster guardian model to optimize the internalization of Pancasila values and cadet identity formation.